PATHOGENETIC MECHANISMS OF FORMATION AND PROGRESSION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Кулинич-Міськів, М. О.; Островський, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
An overview of the literary problems of the pathogenesis of chronic obstructive pulmonary disease. Presented recommendations "Global Strategy: diagnosis, treatment and prevention of COPD (GOLD), European Respiratory Society (ERS), American Thoracic Society (ATS) and a protocol of care for diagnosis and treatment of COPD. The importance of using modern technologies in the diagnosis of chronic Obstructive Lung Disease. The analysis of scientific literature demonstrates the new views on the pathogenesis of chronic obstructive pulmonary disease, as a multi-pathology, which causes structural changes of airway dysfunction muсoсyliar clearance, inflammatory immune response mediated by the respiratory tract, which in sum leads to dysfunction of respiratory and Development major system components.